THE EFECT OF BIRTHING BALL FOR ANXIETY AND PAIN IN LABOR - Melicha Kristine Simanjuntak (Jambura Journal of Health Sciences and Research, 2022)
Physical and psychological factors are one of the causes of mortality and morbidity in pregnant and childbirth women. Physical psychological changes during pregnancy will greatly affect their readiness to face childbirth. Pain and anxiety in labor can be treated with non-pharmacological treatment. One method that can be given is the use of a birthing ball. The purpose of the study was to determine the effect of using a birthing ball on reducing pain intensity and anxiety levels in maternity mothers. This research was conducted at the Tigarunggu Health Center from January to June 2021. The research design was quasi-experimental with a one group pretest-posttest design. The sample is 30 respondents using total sampling technique. The data in this study were processed using the dependent T-Test test. The results of the statistical test showed that there were differences in the level of anxiety in maternity with the average difference of 2.10 and the p-value 0.001. The use of birthing balls also showed a decrease in maternal pain with an average difference of 0.52 and a p-value of 0.02. Based on the results of the study, it was concluded that there was a significant effect on the level of anxiety and pain intensity after the use of birthing balls in women giving birth.